Thermodynamics : - Cengel, Yunus A (McGaw-Hill, 1994)
Each chapter contains numerous worked-out examples that clarify the material and illustrate the use of the basic principles. A consistent and systematic approach is used in the solution of the example problems, with particular attention to the proper use of units. A sketch and a process diagram are included for most examples to clearly illustrate the geometry and the type of process involved.